Macro-economic development of the EU countries in the context of performance and competitiveness of SMEs - Valaskova, Katarina; Nagy, Marek (Business, Management and Economics Engineering, 2023)
Purpose – The paper focuses on the identification of disparities in the development of the macroeconomic environment across the member states of the European Union and problematic factors impacting the business environment’s level.Research methodology – To find the disparities in the development of the EU countries, the TOPSIS method was used. Based on this analysis, the crucial factors influencing the development of the macroeconomic environment were determined. The discriminant analysis was then used to form a model, which could help assess and examine the relationship between the business environment and significant determinants of development.Findings – Based on the methods applied, the determinants influencing the development of the macroeconomic environment and key factors and aspects affecting the rate of development of the economic and business environment were identified and the analysis of the economic and business environment was performed through selected statistical techniques.Practical implications – The analysis confirmed that some countries have certain gaps in its assessment of the dynamics of economic development in EU countries in terms of the sustainability and competitiveness of small and medium-sized businesses, and that the business climate is not entirely conducive to these businesses.Originality/Value – The additional value of the paper is the formation of the model, which helps identify the countries with appropriate business environment and those where the economic development is not sufficiently developed which may be useful for enterprises, investors, and creditors.